2009
DOI: 10.1002/qua.22217
|View full text |Cite
|
Sign up to set email alerts
|

An accurate few‐parameter ground state wave function for the lithium atom

Abstract: ABSTRACT:A simple, seven-parameter trial function is proposed for a description of the ground state of the Lithium atom. It includes both spin functions. Inter-electronic distances appear in exponential form as well as in a pre-exponential factor, and the necessary energy matrix elements are evaluated by numerical integration in the space of the relative coordinates. Encouragingly accurate values of the energy and the cusp parameters as well as for some expectation values are obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 15 publications
(33 reference statements)
3
38
2
Order By: Relevance
“…Among the three, there is a dramatic difference in energy (0.01 hartree) that depends solely on the presence of prefactors. The energy minima for these three functions were evaluated and minimized numerically by Guevara et al 23. The results were similar to those reported here, thereby confirming the accuracy of the analytical evaluation.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Among the three, there is a dramatic difference in energy (0.01 hartree) that depends solely on the presence of prefactors. The energy minima for these three functions were evaluated and minimized numerically by Guevara et al 23. The results were similar to those reported here, thereby confirming the accuracy of the analytical evaluation.…”
Section: Resultssupporting
confidence: 86%
“…For Ps 2 this is a reasonable basis, but it not optimum for Li, where the zero‐order electronic configuration is of the form 1s 2 2s, and a good description of the 2s orbital would be expected to require pre‐exponential term(s) linear in r . An initial study that included such terms was carried out by Guevara et al by a method in which the necessary six‐dimensional integrals were evaluated numerically 23; it showed the importance of the pre‐exponential factors.…”
Section: Introductionmentioning
confidence: 99%
“…In order to check consistency we found that (15) at the critical point Z = Z cr,3e reproduces the ground-state energy of the 2e (14) where all displayed digits assumed to be correct and E (fit) 3e from the fit (15). system E 2e in 6 s.d.…”
mentioning
confidence: 94%
“…As for the lithium atom in its ground state an attempt was already made to find a compact function in the form similar to Hylleraas function ) taking the (anti)symmetrized product of six (modified by screening) Coulomb Orbitals, see Reference 10; recently, it was extended to the Li‐like system at Z > 3 . 3 However, the goal of describing the domain of applicability of QMCC for the Li‐like three‐electronic sequence was not reached.…”
Section: Introductionmentioning
confidence: 99%